Translation, cultural adaptation, and validation of the maternal health promotion behavior scale - Wang, Huiyuan; Zou, Yinting; Guan, Yulan; Li, Zhirong; Ran, Xuerong; Hu, Tingting; Zhai, Jinguo (BMC pregnancy and childbirth, 2025)
United Nations reports show that maternal health is currently deteriorating in most parts of the world, which is far from achieving the 2030 goal of ensuring good maternal health. Adopting health-promoting behaviors during pregnancy is a safe strategy for maintaining and improving maternal and child health. Owing to the high-dimensional, multivariate, and non-directly measurable characteristics of health-promoting behaviors, a comprehensive assessment of these behaviors will help improve population health. The purpose of this study was to translate and cross-culturally adapt Maternal Health Promotion Behavior Scale, which was specifically developed for the maternal population, and to assess the psychometric properties of its Chinese version. This cross-sectional study was conducted between May 2023 and August 2024; convenience sampling was used to select pregnant women in late pregnancy who underwent antenatal checkups. First, the original Maternal Health Promotion Behavior Scale was translated into Chinese and culturally adapted. The psychometric properties of the Chinese version of the Scale were subsequently assessed, including item analysis, content validity, construct validity, internal consistency reliability, and test-retest reliability. A total of 296 pregnant women were included. The Chinese version of the Maternal Health Promotion Behavior Scale consists of 36 scored items in 6 dimensions, with item-level Content Validity Index ranging from 0.83 to 1, and the mean scale-level Content Validity Index of all the items is 0.95. Exploratory factor analysis identified 6 potential factors, and confirmatory factor analysis demonstrated a good fit of the data for this structural equation model. The total Cronbach's α coefficient for the scale was 0.837, McDonald's ω coefficient was 0.848, and test-retest reliability was 0.990. The Chinese version of the Maternal Health Promotion Behavior Scale is a valid and reliable instrument for measuring maternal health-promoting behaviors.